TEMPO-derived spin labels linked to the nucleobases adenine and cytosine for probing local structural perturbations in DNA by EPR spectroscopy - Gophane, Dnyaneshwar B.; Sigurdsson, Snorri Th. (Beilstein Journal of Organic Chemistry, 2015)
Three 2´-deoxynucleosides containing semi-flexible spin labels, namely TA, UA and UC, were prepared and incorporated into deoxyoligonucleotides using the phosphoramidite method. All three nucleosides contain 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) connected to the exocyclic amino group; TA directly and UA as well as UC through a urea linkage. TA and UC showed a minor destabilization of a DNA duplex, as registered by a small decrease in the melting temperature, while UA destabilized the duplex by more than 10 °C. Circular dichroism (CD) measurements indicated that all three labels were accommodated in B-DNA duplex. The mobility of the spin label TA varied with different base-pairing partners in duplex DNA, with the TA•T pair being the least mobile. Furthermore, TA showed decreased mobility under acidic conditions for the sequences TA•C and TA•G, to the extent that the EPR spectrum of the latter became nearly superimposable to that of TA•T. The reduced mobility of the TA•C and TA•G mismatches at pH 5 is consistent with the formation of TAH+•C and TAH+•G, in which protonation of N1 of A allows the formation of an additional hydrogen bond to N3 of C and N7 of G, respectively, with G in a syn-conformation. The urea-based spin labels UA and UC were more mobile than TA, but still showed a minor variation in their EPR spectra when paired with A, G, C or T in a DNA duplex. UA and UC had similar mobility order for the different base pairs, with the lowest mobility when paired with C and the highest when paired with T.
Keywords: aminoxyl radical; ESR spectroscopy; nitroxide; nucleic acids; site-directed spin labeling (SDSL); spin labels; structure-dependent dynamics